Response of Plant Growth and Green Mustard (Brassica juncea L.) Yield Upon the Application of Agrobost Liquid Organic Fertilizer - Sulastri Sulastri; Hery Sutejo; Abdul Fatah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The aim of research was to determine the effect of Agrobost liquid organic fertilizers on the growth and yields of greens mustard, and to find the proper concentration of Agrobost liquid organic fertilizer to obtain the highest yield of green mustard.The research was conducted in Sumber Rejo Village, Sub.district of Sekolaq Darat, West Kutai Regency.  It was conducted from February 2016 to April 2016.The research used a single factor in a completely randomized design (CRD).  The research factor wasan Agrobost Liquid Organic Fertilizer (A), with six replications.  It consisted of six treatments, namely: no application of Agrobost liquid organic fertilizer or control (a0), 2 ml/l water (a1), 4 ml/l water (a2), 6 ml/lwater (a3), 8 ml/l water (a4), and 10 ml/lwater (a5).The research results revealed that the Agrobost liquid organic fertilizer treatment affected very significantly on the crop height at 2, 3, and 4 weeks after planting, leaf number at 2, 3, and 4 weeks after planting, and fresh weight per crop. The highest parameters observed (crop height, leaf number, and fresh weight per crop) were attained at a5 teratment. The highest fresh weight was attained at a5 treatment, namely 250.67 g.  Meanwhile, the lowest one was attained at a0 treatment, with only 61.83 g.